2023
DOI: 10.3389/fncel.2023.1085690
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy analysis of astrocyte-synapse interactions shows altered dynamics in an Alzheimer’s disease mouse model

Abstract: IntroductionAstrocyte-synapse bi-directional communication is required for neuronal development and synaptic plasticity. Astrocytes structurally interact with synapses using their distal processes also known as leaflets or perisynaptic astrocytic processes (PAPs). We recently showed that these PAPs are retracted from hippocampal synapses, and involved in the consolidation of fear memory. However, whether astrocytic synaptic coverage is affected when memory is impaired is unknown.MethodsHere, we describe in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
(66 reference statements)
1
8
0
Order By: Relevance
“…This might be relevant in the WT‐ES group at 4 months as well as APP/PS1 groups (w/wo ES exposure) at 10 months, where we found astrocytic enrichment of differentially expressed proteins. Such potential alterations to PAP motility at the synapse could affect their abilities to regulate extra‐synaptic neurotransmitter diffusion, 12 in line with our recent findings that astrocytes in APP/PS1 mice do not show the activity‐induced retraction from the synapse as observed in WT animals 78 . This is not expected to be due to an increase in astrocyte number, as supported by our total Vimentin coverage data and our previous work on the GFAP coverage and density 17 …”
Section: Discussionsupporting
confidence: 84%
“…This might be relevant in the WT‐ES group at 4 months as well as APP/PS1 groups (w/wo ES exposure) at 10 months, where we found astrocytic enrichment of differentially expressed proteins. Such potential alterations to PAP motility at the synapse could affect their abilities to regulate extra‐synaptic neurotransmitter diffusion, 12 in line with our recent findings that astrocytes in APP/PS1 mice do not show the activity‐induced retraction from the synapse as observed in WT animals 78 . This is not expected to be due to an increase in astrocyte number, as supported by our total Vimentin coverage data and our previous work on the GFAP coverage and density 17 …”
Section: Discussionsupporting
confidence: 84%
“…It is important to mention that this conclusion is based on 2D‐analysis. Therefore, we may have missed synapses that were in contact with an astrocyte if the astrocyte process was not present in the cutting plane used for analysis (see Kater et al, 2023 for a more extensive discussion of this issue). Nevertheless, the number of synapses contacted by an astrocyte in wildtype mice in our study (49%) was close to the 57% observed using 3D EM analysis (Ventura & Harris, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For synapses in which the astrocyte contacted the synaptic cleft, the shortest distance between the PAP tip and the PSD was measured. The length of the PAP tip was measured using a standardized method (Kater et al, 2023). Firstly, the base of the PAP tip was determined and a straight line was drawn from edge to edge.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that PAP-spine contacts are selectively restructured in an activity-dependent manner as a function of LTP. Given synaptic remodeling is associated with learning and memory ( Caroni et al, 2012 ; Badia-Soteras et al, 2022 ), and morphological plasticity of PAPs was found to be impaired in a mouse model of Alzheimer Disease ( Kater et al, 2023 ), astrocytic GPCR-mediated PAP motility is likely a key mechanism mediating learning and memory processes.…”
Section: Astrocyte Participation At the Synapsementioning
confidence: 99%